Implementation of optimal solution for network lifetime and energy consumption metrics using improved energy efficient LEACH protocol in MANET - Prasad A. Y.; R. Balakrishna (Universitas Ahmad Dahlan, 2019)
In current scenarios MANET mainly focus on low power battery operated devices. Moreover in a MANET transmission of large data consumes more energy that affects the performance of network, energy consumption, throughput, end to end delay, and packet overhead. The sum of these parameter metrics measure must be taken into account to increase the life-time and network energy efficiency. The main constraint in WSN is due to the restricted power in a node, which cannot be substituted. The node senses the data and it is moved towards the sink. This action of data movement needs to be efficient and the usage of battery in the sensor node requires to be efficiently employed to improve the network lifetime. The development of the energy efficient algorithms is of primary concern in the research arena of MANET. In any network, most of the routing protocols are focused directly to collect and bifurcate the large data for long distance communication. The prime goal of this research focused to identifies and survey more suitable routing protocol for MANET. That consumed less energy and increase life time of network. In this paper the author made on attempt on improved energy efficient LEACH protocol for MANET to reduce the energy dissipation that to life time of the network during the data transmission between source nodes and destination nodes.